Dissimilarity of increased phosphatidylserine-positive microparticles and associated coagulation activation in acute coronary syndromes. Issue 5 (August 2016) - Liu, Yan; He, Zhangxiu; Zhang, Yan; Dong, Zengxiang; Bi, Yayan; Kou, Junjie; Zhou, Jin; Shi, Jialan
Abstract : Objective: We evaluated cellular origin, numbers, and procoagulant activity of phosphatidylserine-positive microparticles (MPs) among subgroups in acute coronary syndromes (ACS). Materials and methods: Parameters were measured on admission, days 1 (within 24 h of admission), 2, 3, and 7. All ST-elevated myocardial infarction (STEMI) patients presented more than 3 h from symptom onset and received fibrinolysis treatment; controls included unstable angina and non-STEMI patients as well as healthy controls. Phosphatidylserine-positive MPs were detected by flow cytometry, whereas procoagulant activity was assessed by coagulation time, purified coagulation complex assays, and fibrin formation. MP-induced fibrins were visualized by confocal microscopy. Results: On admission, the total MP count was ∼2.5-fold higher in the ACS groups compared with the healthy controls ( P <0.05), primarily originating from platelets and endothelial cells, and there were no significant differences among ACS subgroups. Specifically, leukocyte-derived and erythrocyte-derived MPs were higher in the STEMI group compared with unstable angina and non-STEMI groups (both P <0.05). Further, MPs from the ACS groups reduced coagulation time by 27.5% and induced intrinsic and extrinsic FXase, prothrombinase, and fibrin formation by 2.8-, 2.3-, 2.5-, and 1.7-fold, respectively ( P <0.05 for all), whereas blocking phosphatidylserine with lactadherin inhibited ∼70% of procoagulant activity. MP number and concomitant coagulation decreased significantly by day 2 and continued to decrease gradually during the recovery period. Conclusion: This study shows that MP characteristics from circulating blood may be used as prognostic indicators to reflect the origin cell of activation and thrombophilic states found in ACS subgroups.